2022
DOI: 10.3390/diagnostics12081874
|View full text |Cite
|
Sign up to set email alerts
|

Association of Handgrip Strength with Diabetes Mellitus in Korean Adults According to Sex

Abstract: Diabetes mellitus (DM) is known to lead to many diseases such as cardiovascular disease and chronic kidney diseases. Therefore, it is essential to find diagnostic tools to prevent DM. This study aimed to find the association between handgrip strength and the prevalence of diabetes mellitus (DM) in Korean adults with respect to sex and menopause. A total of 26,536 participants (12,247 men, 6977 premenopausal women, and 7312 postmenopausal women) aged >19 years were recruited. The study population was divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…Handgrip strength is a prognostic indicator for metabolic syndrome, hypertension and diabetes (28)(29)(30). However, these studies commonly suggested that HGS be a practical tool to evaluate these comorbidities in high-risk groups rather than healthy groups.…”
Section: Discussionmentioning
confidence: 99%
“…Handgrip strength is a prognostic indicator for metabolic syndrome, hypertension and diabetes (28)(29)(30). However, these studies commonly suggested that HGS be a practical tool to evaluate these comorbidities in high-risk groups rather than healthy groups.…”
Section: Discussionmentioning
confidence: 99%
“…Jumlah lemak pada laki-laki 15-20% dari berat badan sedangkan perempuan 20-25% dari berat badan. Jadi peningkatan kadar lemak pada perempuan lebih tinggi dibandingkan lakilaki, sehingga faktor terjadinya diabetes mellitus pada perempuan 3-7 kali lebih tinggi dibandingkan pada laki-laki yaitu 2-3 kali (15) (21). Penurunan kekuatan otot berhubungan dengan peningkatan kadar penanda inflamasi (tumor necrosis factoralpha (TNF-α), interleukin-6 (IL-6), dan Creactive protein (CRP)), yang dapat menginduksi perkembangan diabetes (21).…”
Section: Jenis Kelaminunclassified
“…However, the study participants were limited to obese women with an average age of approximately 70 years, and the number of participants was relatively low (approximately 600) [8]. Lee et al reported an inverse association between RGS and prevalence of diabetes mellitus (DM) in a study targeting a Korean population [9]. The number of participants was approximately 20,000, which gave the study the advantage of being a large-group study.…”
Section: Introductionmentioning
confidence: 99%
“…The number of participants was approximately 20,000, which gave the study the advantage of being a large-group study. However, since it was a cross-sectional study, the relationship between RGS and the incidence of DM could not be determined [9]. Wander et al studied the relationship between HGS and occurrence of diabetes among Japanese-Americans who had not been diagnosed with diabetes in the United States and found an inverse association between HGS and the incidence of diabetes in the leaner group with a low BMI [10].…”
Section: Introductionmentioning
confidence: 99%